Infrastructure & Ops Hour. (O'Reilly Media, Inc., 2022)
Join us for a special conversation with Sam Newman, Manuel Pais, and Matthew Skelton, where they'll discuss their best-selling book, Team Topologies, and what's next for the future of building software. Team topologies is the leading approach to organizing business and technology teams for fast flow, providing a practical, step-by‑step, adaptive model for organizational design and team interaction. They'll also spend a few minutes covering the trends that are influencing infrastructure, then tell you what you need to know to stay ahead of the curve. What you'll learn and how you can apply it Explore the origins and need for team topologies See what's coming next for infrastructure and ops This recording of a live event is for you because... You want to learn about team topologies and how to implement them at your organization. You're looking for ways to improve your software delivery time and team structure. Recommended follow-up: Read "Business Benefits, Team Topologies, and Pitfalls of DevOps" (book chapter) Watch Kubernetes Is Not Your Platform--It's Just the Foundation (Superstream video with Maneul Pais) Read The DevOps Handbook (book) Read Accelerate (book).